Penerapan Teknologi Informasi Berbasis Komputer Pada Organisasi Perusahaan Peluang Dan Tantangan - Ellitan, Lena (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2002)
In general, information is main sources for people today. If words are the best weapon then the information technology is revolution took for companies for companies. Globalization era in which hallmarked with a neck to neck competition among companies then as competitive strategy tool is used the information technology. The application of information technology goes in to most aspect of organization if whether in business activities or processes. This emerges the hierarchical erosion and downsizing virtual organization, virtual offices, a paperless revolution and mimicking brains. These might be impact on the business organization whether an opportunity or a challenge. The purpose of this paper is to figure out the possible impact that rises whether it is an opportunity or a challenge. Keywords: information technology, hierarchical erosion, virtual office, paperless revolution,. Mimicking brains